PENGARUH KELENGKAPAN IMUNISASI DASAR TERHADAP TUMBUH KEMBANG BAYI (0-1 TAHUN) YANG LAHIR PADA MASA PANDEMI COVID-19 - Zuliyana Zuliyana; Ervinawati Ervinawati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Abstract : Basic immunization is one of the infectious disease prevention programs for children. Basic immunizations given in full will affect the stage of growth and development in children. Normal growth and development in accordance with his age is very good for the continuation of life in the future. The Covid-19 pandemic limits us from doing activities outside the home and has an impact on the continuity of health services, one of which is a decrease in basic immunization visits. The purpose of this study was to determine the effect of completeness of basic immunization on the growth and development of infants (0-1 years) born during the Covid-19 pandemic. The research method used is an analytical observational research design with a cross sectional approach. The research was conducted at BPM Bd. Elviana. The respondents used were infants (0-1 years) who were born during the Covid-19 pandemic. The results of the study show that there is a relationship between the completeness of immunization and the growth of babies born during the Covid-19 pandemic with a p value = 0.012 < 0.05. And there is no relationship between completeness of immunization and the development of babies born during the Covid-19 pandemic with p value = 0.066 > 0.05Keywords : Basic Immunization, growth, development, baby, covid-19